The Economics of Enforcing Market-Based Pollution Control (2011)
Introduction. I. Firm behavior and market. Equilibrium under cap-and-trade. II. Optimal enforcement of cap-and-trade. III. Dynamic emissions trading. IV. Lessons for cap-and-trade policies for greenhouse gas emissions. V.Conclusion. References.